2005
DOI: 10.1038/sj.pcan.4500778
|View full text |Cite
|
Sign up to set email alerts
|

Does needle size matter? Patient experience of luteinising hormone-releasing hormone analogue injection

Abstract: To determine whether needle size influences a patient's perception of pain, 50 patients requiring hormonal manipulation for prostate cancer were blindfolded and randomised to receive two goserelin ('Zoladex') or two leuprorelin ('Prostap') injections, using 16-or 23-gauge needles, respectively. Median visual analogue scale pain scores for the first injections of goserelin and leuprorelin were below the level of clinical significance and were not statistically different. Mean administration time for goserelin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The use of a 16-gauge needle for goserelin acetate rather than a 23-gauge needle of leuprorelin acetate may influence their results [1]. On the other hand, Montgomery et al [2] demonstrated that there was no significant difference in pain intensity between goserelin acetate and leuprorelin acetate when patients received them in a blinded manner. It is important to note that the majority of patients who participated in these two studies reported a VAS pain score \13 mm, which may be considered clinically insignificant [3,4].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The use of a 16-gauge needle for goserelin acetate rather than a 23-gauge needle of leuprorelin acetate may influence their results [1]. On the other hand, Montgomery et al [2] demonstrated that there was no significant difference in pain intensity between goserelin acetate and leuprorelin acetate when patients received them in a blinded manner. It is important to note that the majority of patients who participated in these two studies reported a VAS pain score \13 mm, which may be considered clinically insignificant [3,4].…”
Section: Discussionmentioning
confidence: 97%
“…A randomized crossover study demonstrated that patients preferred injection of leuprorelin acetate via a smaller needle than goserelin acetate using a larger needle [1]. However, in contrast, another study showed that if injection was performed with the patient blinded, injection pain intensity was not significantly different between leuprorelin acetate administration with a small needle and goserelin acetate administration using a larger needle [2]. Even if injection pain is tolerable, it is important for patients to have minimum injection pain associated with goserelin acetate.…”
Section: Introductionmentioning
confidence: 88%
“…Patients receiving Lupron ® Depot may experience pain at the injection site lasting up to 2 days, large abscesses, and bruising. However, there was no statistically signifi cant difference in pain experienced on injection of goserelin and leuprorelin when patients were unaware of needle size (Montgomery et al 2005).…”
Section: Mechanism Of Actionmentioning
confidence: 90%
“…Indeed, small needle size has been associated with a lower frequency of pain in healthy volunteers (4) and in a lower intensity of pain in patients with multiple sclerosis (5). However, other studies have shown pain intensity to be either only slightly affected (6) or unaffected by needle size (7,8).…”
mentioning
confidence: 97%